Descriptive Analysis of Science Pre-Service Teachers’ Technological, Pedagogical, and Content Knowledge (TPACK) - Gemcer D. Selda (Research Synergy Foundation, 2026)
This study explores the integration of technology in Philippine teacher education with a focus on the distinctive context of Mindoro. Using the TPACK framework, this study assesses pre-service teachers’ competence in integrating content, pedagogy, and technology into their instructional practices. Results show that the pre-service teacher population is largely young and female, with diverse income levels and specializations. Both pre-service teachers and cooperating teachers report strong development across TPACK domains, especially in Technological Knowledge. Income and specialization emerge as significant factors influencing competency levels, while age and gender show minimal effects. Differences between self-assessments and cooperating teacher evaluations highlight the need for more targeted training and curriculum improvements. Among the three specializations, Mathematics pre-service teachers rated themselves higher than their cooperating teachers did. In contrast, English and Science pre-service teachers received higher ratings from their cooperating teachers than from their own self-assessments. The study recommends refining admission policies, strengthening professional development programs, and enhancing curriculum content better to address competency gaps and support effective technology-enhanced teaching.